2016
DOI: 10.3389/fnagi.2016.00247
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of the Default Mode Network in Drug-Naïve Parkinson’s Disease with Mild Cognitive Impairments: A Resting-State fMRI Study

Abstract: Objective: Cognitive impairments are common in Parkinson’s disease (PD) and can even occur in the early stages. The default mode network (DMN) is highly relevant for cognitive processes; however, it remains largely unknown if changes in the DMN connectivity are related to the cognitive decline in drug-naïve early stage PD patients with a mild cognitive impairment (MCI). This study used resting-state functional MRI (fMRI) to explore the brain connectivity of the DMN in early stage drug-naïve PD patients with MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 42 publications
6
50
0
1
Order By: Relevance
“…The SMG is also part of the inferior parietal lobe, the core brain region of the default mode network, which is highly relevant for cognitive processes (Raichle et al, ). Previous structural and functional studies found cortical thinning and reduced functional connectivity in the inferior parietal lobe in PD‐MCI (Hou et al, ; Pereira et al, ). Our results align with the pattern of posterior hypoperfusion and hypometabolism characterized by prolonged ATT and decreased CBF in PD, PD‐MCI, and PD‐D previously detected by ASL, SPECT, and PET studies (Al‐Bachari et al, ; Al‐Bachari et al, ; Eckert, Tang, & Eidelberg, ; Lin et al, ; Melzer et al, ; Nobili et al, ; Pappata et al, ; Syrimi et al, ), which can be assumed to contribute to impaired cognition.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The SMG is also part of the inferior parietal lobe, the core brain region of the default mode network, which is highly relevant for cognitive processes (Raichle et al, ). Previous structural and functional studies found cortical thinning and reduced functional connectivity in the inferior parietal lobe in PD‐MCI (Hou et al, ; Pereira et al, ). Our results align with the pattern of posterior hypoperfusion and hypometabolism characterized by prolonged ATT and decreased CBF in PD, PD‐MCI, and PD‐D previously detected by ASL, SPECT, and PET studies (Al‐Bachari et al, ; Al‐Bachari et al, ; Eckert, Tang, & Eidelberg, ; Lin et al, ; Melzer et al, ; Nobili et al, ; Pappata et al, ; Syrimi et al, ), which can be assumed to contribute to impaired cognition.…”
Section: Discussionmentioning
confidence: 84%
“…The SMG is also part of the inferior parietal lobe, the core brain region of the default mode network, which is highly relevant for cognitive processes (Raichle et al, 2001). Previous structural and functional studies found cortical thinning and reduced functional connectivity in the inferior parietal lobe in PD-MCI (Hou et al, 2016;Pereira et al, 2014). Melzer et al, 2011;Nobili et al, 2009;Pappata et al, 2011;Syrimi et al, 2017), which can be assumed to contribute to impaired cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have reported a range of abnormal brain areas that are associated with cognitive decline in PD. For example, R-fMRI functional connectivity analysis has suggested patients of PD with MCI could be characterized by dysfunction in the default mode network and dorsal attention network ( Baggio et al, 2015 ; Hou et al, 2016 ). A longitudinal study using task-fMRI has reported reduction of BOLD signals that are related to working-memory brain activity in the right fusiform gyrus and right vermis in patients of PD with MCI ( Ekman et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…A structural MRI study reported that, compared with PD-CN, patients with PD-MCI had more severe cortical thinning in the frontal and temporo-parietal cortices [21]. One study of de novo, newly diagnosed PD, which incorporated brain connectivity analysis of resting-state fMRI, revealed that patients with PD-MCI showed decreased functional connectivity between posterior cingulate cortex and posterior IPL [22].…”
Section: Dysfunction Of Visuospatial Working Memory In Pd-mci: Roles mentioning
confidence: 99%